2014
DOI: 10.1007/s11205-014-0825-1
|View full text |Cite
|
Sign up to set email alerts
|

Fatalism and Well-Being Across Hispanic Cultures: The Social Fatalism Scales (SFS)

Abstract: El acceso a la versión del editor puede requerir la suscripción del recurso Access to the published version may require subscription Dear Author,Here are the proofs of your article.• You can submit your corrections online, via e-mail or by fax.• For online submission please insert your corrections in the online correction form. Always indicate the line number to which the correction refers.• You can also insert your corrections in the proof PDF and email the annotated PDF.• For fax submission, please ensure th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 43 publications
3
27
0
8
Order By: Relevance
“…Thus, we predict that well-being mediates the relationship between post-traumatic dysfunctional cognitions and DTS. More specifically, we expect that PWB (an individual well-being construct [ 35 ] mediates the relationship between NCS and DTS, and that SoWB (a macrosocial well-being construct [ 23 ]) mediates the relationship between NCW and DTS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we predict that well-being mediates the relationship between post-traumatic dysfunctional cognitions and DTS. More specifically, we expect that PWB (an individual well-being construct [ 35 ] mediates the relationship between NCS and DTS, and that SoWB (a macrosocial well-being construct [ 23 ]) mediates the relationship between NCW and DTS.…”
Section: Resultsmentioning
confidence: 99%
“…This instrument consists of five scales (social integration, social acceptance, social contribution, social actualization and social coherence), which in previous studies have shown good internal consistency [ 23 ]. The proposed five-dimensional structure with a second order general factor has been tested using confirmatory factor analysis with Spanish samples [ 35 ]. In the present study we computed only the sum of all items as a global indicator of social well-being (Cronbach’s α = .90; M = 4.56; SD = .94).…”
Section: Methodsmentioning
confidence: 99%
“…Martín-Baró (1998) apontou a necessidade de entender o fatalismo como um fenômeno psicossocial, que está associado às "... condições econômicas, políticas e culturais de cada sistema social" (p. 82). A percepção da incerteza, a submissão, o pessimismo (Blanco & Díaz, 2007;Díaz, Blanco, Bajo, & Stavraki, 2015;Martín-Baró, 1998;Vallejo Martín et al, 2017), típicos do fatalismo, não se apresentam de modo absoluto ao longo do tempo. Contrariamente, sofrem influências dos modos de organização da sociedade, dos processos de exclusão social e desigualdade que se perpetuam e se agravam ao longo do tempo.…”
Section: Introductionunclassified
“…Esparza, Wiebe, e Quiñones (2015) identificaram que, nos últimos 30 anos, tem ocorrido um crescente interesse sobre o construto fatalismo no interior das investigações sobre psicologia da saúde e psicologia da personalidade. Isto se deve, em grande parte, a associação identificada entre fatalismo e comportamentos de saúde (Cohn & Esparza del Villar, 2015) e fatalismo e satisfação com a vida (Díaz et al, 2015). Pode-se dizer que a interferência das crenças fatalistas sobre a saúde e a percepção de bem estar se dá em duas grandes vias, que estão entrelaçadas.…”
Section: Introductionunclassified
See 1 more Smart Citation